Effects of metalloids and heavy metals on flora in a former antimony mine area - Bentellis, Alima; Rached, Oualida (Biológia, 2025)
Soils on the banks of a wadi in the area of a former antimony mine, which closed in 1952, were the subject of almost complete physicochemical characterisation. The soils were found to contain very high concentrations of antimony (Sb) and arsenic (As), as well as being contaminated by other metals (lead (Pb), copper (Cu) and zinc (Zn)). These soils are mainly home to steppe species such as Artemisia herba-alba Asso, Lygeum spartum Loefl. ex L. and Thymus algeriensis Boiss. & Reut. This study aimed to identify the metals and metalloids most harmful to vegetation that must be stabilised or removed from contaminated soils. The study also aimed to identify the plant species that prefer metalliferous soils for use in phytostabilisation of polluted soils. To this end, floristic surveys were conducted in each soil sampling plot in which the abundance of each species present was recorded. We calculated species richness and Shannon's diversity index. Stepwise multiple regression analyses were conducted to determine the effects of mine proximity, metalloids and metals on plant species diversity and plant species richness, and the impact of mining on plant species presence. The results demonstrated that arsenic (As) (450 mg.kg −1 maximum) and cadmium (Cd) (1.1 mg.kg −1 maximum) had a very significant and important impact on species richness, while mining proximity had a significant effect on species diversity. Mining proximity has indisputably affected the presence of several plant species. Our research clearly shows that several species, including Carthamus lanatus L ., Centaurea sicula Leyss. ex DC . and Hippocrepis unisiliquosa L., prefer soils close to the mine and therefore those with the highest levels of metals and metalloids, particularly As and Cd. These species could therefore be suitable for soil remediation in the Sb mining area. Surprisingly, Sb (2600 mg.kg −1 maximum) at high concentrations seems to be less toxic than Cd at low concentrations. It would therefore appear that the study area requires more urgent action to eliminate or stabilise As and Cd than Sb. For soil stabilisation, the most effective approach is to use mainly species that prefer soils close to the mine.